Dysocjacja jako hard case w systemie prawa karnego materialnego - Helios, Joanna; Jedlecka, Wioletta (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Dissociation is a borderline case, remaining at the interface of law and neuroscience. The relation of law and neuroscience is special, because at its junction a number of problems occur which the legal system is not fully prepared to solve.In the article the authors discuss two issues: the concept of dissociation and the relationship between dissociation, sanity and responsibility. In the authors’ opinion the state of dissociation is located just within the category referred to in the Penal Code as “other disturbances of mental activity.”
Keywords: dysocjacja; hard case (cięzki przypadek); system prawa karnego; poczytalność